The ANALYSIS OF PORT SERVICE LEVY COLLECTION STRATEGY IN AN EFFORT TO INCREASE THE REGIONAL LEVY INCOME FOR NORTH BUTON REGENCY IN 2016-2020 - Wa Ode Lutfian; Debi Kartika Masuli; Rahma Yeni; Antoni Ludtfi Arifin (Jurnal Widya Akuntansi dan Keuangan, 2023)
This study aims to analyze the strategy for port service levy collection in an effort to increase the regional levy income for North Buton Regency in 2016-2020 and the inhibiting and driving entities in the port service levy collection. The research method used in this study was a qualitative descriptive method. The author used primary data in the form of interview results and secondary data in the form of target data and the realization of port service levy income. The results showed that the strategy for port service levy collection in an effort to increase the regional levy income for North Buton Regency in 2016-2020 had not been carried out properly. This is caused by various obstacles, including the lack of human resources, the lack of facilities and infrastructure, and lack of supervision.